login
a(n) = f(f(n+1)) - f(f(n)), where f(0)=0, and for m>0, f(m) = phi(m) = A000010(m).
1

%I #13 Jun 25 2022 21:51:49

%S 1,0,0,0,1,-1,1,0,0,0,2,-2,2,-2,2,0,4,-6,4,-2,0,0,6,-6,4,-4,2,-2,8,-8,

%T 4,0,0,0,0,-4,8,-6,2,0,8,-12,8,-4,0,2,12,-14,4,-4,8,-8,16,-18,10,-8,4,

%U 0,16,-20,8,-8,4,4,0,-8,12,-4,4,-12,16,-16,16,-12,4,-4,4,-8,16,-8,2,-2,24,-32,24,-20,12,-8,24,-32,16,-4,-4,6

%N a(n) = f(f(n+1)) - f(f(n)), where f(0)=0, and for m>0, f(m) = phi(m) = A000010(m).

%H Alois P. Heinz, <a href="/A111409/b111409.txt">Table of n, a(n) for n = 0..10000</a>

%p a:= n-> (f-> f(f(n+1))-f(f(n)))(numtheory[phi]):

%p seq(a(n), n=0..100); # _Alois P. Heinz_, Jun 20 2022

%Y Cf. A000010 (phi).

%Y First differences of A010554.

%K sign

%O 0,11

%A _N. J. A. Sloane_, Nov 12 2005

%E Definition corrected by _N. J. A. Sloane_, Feb 14 2018